The Art of Prehistoric Textile Making The development of craft traditions and clothing in Central Europe - Grömer, Karina (Naturhistorisches Museum Wien, 2016)
Textiles, textile production and clothing were essentials of living in prehistory, locked into the system of society at every level - social, economic and even religious. Textile crafts not only produced essential goods for everyday use, most notably clothing, but also utilitarian objects as well as representative and luxury items. Prehistoric clothing and their role in identity creation for the individual and for the group are also addressed by means of archaeological finds from Stone the Iron Age in Central Europe.